(untitled) (Indian Journal of Arid Horticulture, 2025)
geographical area of the country. The hot arid regions spread over the states of Rajasthan, Gujarat, Andhra Pradesh, Punjab, Haryana, Karnataka and Maharashtra which are characterized by hostile agro-climate and fragile eco-system (Anon., 1998-99). Despite the various bio- physical constraints, the hot arid areas of western Rajasthan like Bikaner district offers very good opportunities for ber based farming system including rearing of cow, buffalo, sheep, goats and camels with ber production. Monocropping is a very risky profession in hot arid regions of western Rajasthan due to frequent occurrence of drought, which results in famine. Therefore, people of this region adopt subsistence and mixed farming system i.e. crop production with livestock rearing. It has been observed that the ber production with livestock rearing is a very dominant emerging farming system in western Rajasthan. However, the authentic information about recent development in ber based farming system practiced in arid eco-system of western Rajasthan are not available. Such information may be of paramount importance for strategic plan formulation for further encouragement of ber based farming system and other alike programmes for the farmer’s welfare in arid regions of the country.